2018
DOI: 10.4103/1319-2442.239663
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcome of postpartum acute kidney injury requiring dialysis: A single-center experience from North India

Abstract: Postpartum acute kidney injury (AKI) is one of the serious complications of pregnancy and is associated with high mortality and morbidity. We conducted this study to determine the characteristics and outcome of the most severe form of postpartum AKI requiring dialysis. This prospective, observational study was conducted in Sawai Man Singh Medical College, Jaipur. All postpartum female suffering from AKI requiring dialysis between July 2014 and December 2016 were included in the study. Demographic, clinical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Recent studies report that preeclampsia is associated with an increased risk of remote cardiovascular disease and ESRD (94). In the past, AKI was also considered to be a completely reversible syndrome, however, in recent years, several studies have indicated that AKI may increase the risk of developing CKD, incurring continued kidney damage, or requiring dialysis even after delivery (28,47,95). Estimates of long-term prognosis after AKI in pregnancy are limited by inconsistent definitions and follow-up duration.…”
Section: Long Term Consequences Of Pr-akimentioning
confidence: 99%
“…Recent studies report that preeclampsia is associated with an increased risk of remote cardiovascular disease and ESRD (94). In the past, AKI was also considered to be a completely reversible syndrome, however, in recent years, several studies have indicated that AKI may increase the risk of developing CKD, incurring continued kidney damage, or requiring dialysis even after delivery (28,47,95). Estimates of long-term prognosis after AKI in pregnancy are limited by inconsistent definitions and follow-up duration.…”
Section: Long Term Consequences Of Pr-akimentioning
confidence: 99%
“…Mortalitas yang meningkat ini berdasarkan studi tersebut disebabkan tingginya angka sepsis pada kehamilan yang direfleksikan melalui Sequential Organ Failure Assessment (SOFA). 4 Namun, berdasarkan Vinturache, dkk bahwa terjadi perubahan angka insiden di negara berkembang dan negara maju. Didapatkan angka mortalitas AKI pada kehamilan terhadap ibu dan janin sudah mulai menurun di beberapa negara berkembang tetapi masih meningkat di negara maju.…”
Section: Pendahuluanunclassified